Factors Influencing Sport Education in Character Formation and Students' Mental Health - Reni Silviah (Siber International Journal of Sport Education, 2024)
Literature Reviews Factors that influence sport education in character building, and mental health is a scientific article with the aim of analyzing whether sport education influences character building, and mental health. Qualitative approach method with literature review method to explore and analyze the relationship between character, mental health and sports education. The results of this article are: 1) Sport Education influences character building, 2) Sport Education influences improving mental health. Apart from these 2 exogenous variables that influence the endogenous variable Sport Education, there are many other factors including the quality of education, teacher competence, teacher leadership.